Análise do choque de risco-país sobre os ciclos econômicos brasileiros pós-regime de metas para a inflação - Borges, Wesley Augusto de Freitas (2019)
This study sought to analyze the impact of the country risk shock on the Brazilian economic cycles post-inflation targeting regime. For this, we used a SOE-RBC model proposed by Schmitt-Grohé and Uribe (2003) modified to estimate parameters by means of Bayesian methods. The results suggest that the country risk shock mainly explains the short-term oscillations of foreign debt and investment and a small part of the short-term oscillations of the capital stock, while the short-term oscillations of the other variables are explained by the productivity shock. In addition, it is considered that a positive shock in the country risk or possible downgrade by a rating agency would have a greater impact on investments and national external debt. When conducting a sensitivity analysis on the external debt impact coefficient on the interest rate, it is found that a lower ratio between net external debt and output mitigates the negative impacts of an increase in country risk, especially in product, investment, hours worked, salary, and capital stock. Given the recent concern to control the trajectory of public debt since Constitutional Amendment n° 95, there is an attention point in the indication of a vicious cycle between the debt increase and the country risk that can be considered in the elaboration of the next Brazilian public and economic policies. However, there is an important trade-off between the possible loss of autonomy and the national sovereignty by the monetary authority when it conforms to the recommendations of evaluating or supranational agencies that need further investigation.